Penerapan Pembelajaran Kooperatif Tipe Take and Give untuk Meningkatkan Hasil Belajar Kognitif Siswa Sekolah Dasar - Vicky Budi Utomo; Dedi Kuswandi; Saida Ulfa (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
This study aims to improve the cognitive learning outcomes of fifth grade students of SDN Arjowilangun 04 Malang Regency in the academic year 2014/2015. This type of research is a classroom action research consisting of two cycles. Data collection techniques using observation, questionnaires, interviews, and tests. The results showed that there was an increase in student learning outcomes from cycle I to II using the take and give type of cooperative learning. This can be seen from the completeness of student learning outcomes in cycle I by 66% and increased to 93% in cycle II.